REMOVAL OF IRON FROM AQUEOUS SOLUTION BY RICE HUSK: ISOTHERM AND KINETIC STUDY - Monik Kasman; Shaliza Ibrahim; Salmariza Salmariza (Institution for Industrial Research and Standardization of Industry - Padang, 2012)
This work was focused on iron adsorption by rice husk. The use of rice husk for the removal of iron from aqueous solution at different contact time, pH, adsorbent doses and initial iron concentration was investigated. This study was also aimed to recognize the mechanisms that govern iron removal, and to find an appropriate isotherm and kinetic model in batch process. The equilibrium adsorption isotherms have been analyzed by Freundlich and Langmuir model. The pseudo-first, and pseudo-second order kinetic models have been used to investigate the mechanism of adsorption and potential rate controlling steps. The equilibrium data fitted well to Freundlich model and mechanism of adsorption described well to pseudo first order kinetic. The iron adsorption process was highly dependent on pH, dosage and initial concentration dependent. Iron was reduced higher with decrease in iron concentration and increase in rice husk dosage. The suitable contact time for iron removal was found to be 180 minutes.ABSTRAKFokus penelitian ini adalah adsorpsi besi dengan menggunakan adsorban sekam padi. Eksperimen dilakukan dengan memvariasikan waktu kontak, nilai pH, dosis adsorban dan konsentrasi awal besi. Penelitian bertujuan untuk mengamati mekanisme yang mempengaruhi penyisihan besi dan menemukan model isothermal dan kinetika yang tepat untuk proses adsorpsi besi. Kesetimbangan model isotermal dianalisis dengan modelFreundlich dan Langmuir. Model kinetika order pertama dan kedua digunakan untuk mengamati mekanisme adsorpsi dan tahap kontrol kecepatan potensial. Hasil penelitian menunjukan bahwa model adsorpsi yang tepat untuk penyisihan besi adalah model Freundlich dan mekanisme adsorpsi yang sesuai adalah kinetika orde pertama. Prosesadsorpsi besi sangat dipengaruhi oleh pH, dosis adsorban dan konsentrasi awal besi. Persentase penyisihan besi meningkat jika konsentrasi awal besi menurun dan dosis adsorban meningkat. Hasil penelitian menunjukan bahwa adsorpsi besi terjadi dengan baikpada waktu kontak sekurang-kurangnya 180 menit.